A New Historicist Reading Of Islamization And Islamophobia In Selected Contemporary Pakistani Diasporic Fiction Malik - Afzal, Malik Haroon (2022)
Literature and power-politics have a strong connection when it comes to literature’s role in promulgating and propagating a certain narrative which serves the interest of power. Past studies on contemporary Pakistani diasporic fictions tend to explore the themes of Islamization and Islamophobia in terms of their relation with power. There is a dearth of research that have investigated intensively the way the narratives of Islamization and Islamophobia were promulgated and propagated on the pretext of discursive formations, i.e., literary and non-literary. The present study unveils this role of discursive formations with reference to the selected contemporary Pakistani diasporic fiction: Muhammad Hanif’s A Case of Exploding Mangoes and Our Lady of Alice Bhatti, Hanif Kureishi’s The Black Album and My Son the Fanatic, Mohsin Hamid’s The Reluctant Fundamentalist, and Kamila Shamsie’s Home Fire. Since the Cold War, the narratives of Islamization and Islamophobia have been influencing the Muslims globally, especially in Pakistan due to its Islamization program during the Soviet invasion of Afghanistan. The treatment of Muslim identity by the West in both pre and the post-Cold War eras reveals an interesting shift in the Western approach towards Muslims.